Photoelectron multipliers based on avalanche pn - i - pn structures - Lukin, K. A.; Maksymov, P. P.; Cerdeira, H. A. [UNESP] (Springer, 2014)
We present a new physical principle to design an optoelectronic device, which consists of a multilayered semiconductor structure, where the necessary conditions for generation of photoelectrons are met, such that it will enable sequential avalanche multiplication of electrons and holes inside two depletion slabs created around the p - n junctions of a reverse biased pn - i - pn structure. The mathematical model and computer simulations of this Semiconductor Photo-electron Multiplier (SPEM) for different semiconductor materials are presented. Its performance is evaluated and compared with that of conventional devices. The Geiger operational mode is briefly discussed which may be used in Silicon Photomultiplier (SiPM) as an elementary photo detector to enhance its performance.